Mitochondrial Protein PINK1 Positively Regulates RLR Signaling - Zhou, Jun; Yang, Rui; Zhang, Zhaoru; Liu, Qianru; Zhang, Yuanyuan; Wang, Qingqing; Yuan, Hongbin (Frontiers in Immunology, 2019)
The serine/threonine kinase PINK1 controls mitochondrial quality and plays a vital role in the pathogenesis of early-onset Parkinson’s disease. However, whether PINK1 has functions in innate antiviral immunity is largely unknown. Here, we report that viral infection down regulates PINK1 expression in macrophages. PINK1 knockdown results in decreased cytokine production and attenuated IRF3 and NF-B activation upon viral infection. PINK1 promotes the RLR-triggered immune responses in a kinase domain-dependent manner. Furthermore, PINK1 associates with TRAF3 via the kinase domain and inhibits Parkin-mediated TRAF3 K48-linked proteasomal degradation. In addition, PINK1 interacts with YAP1 upon viral infection and impairs YAP1/IRF3 complex formation. Collectively, our results demonstrate that PINK1 positively regulates RIG-I triggered innate immune responses by inhibiting TRAF3 degradation and relieving YAP-mediated inhibition of the cellular antiviral response.RLR